2005
DOI: 10.1111/j.1467-8683.2005.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Ownership, Corporate Governance and Top Management Pay in Hong Kong

Abstract: Top management pay has been the focus of intense scrutiny and debate in many countries. Important issues include how compensation is decided and whether it is a function of performance. The purpose of this study is to examine top management pay in Hong Kong and to investigate how it is affected by firms' ownership and governance characteristics. A distinguishing characteristic of many listed firms in Hong Kong is the large proportion of share capital owned by the directors, and we argue that this moderates top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 45 publications
7
78
3
Order By: Relevance
“…In fact, and as an example of the case of research context potentially accounting for differences in the level of PPS that is observed, Sapp (2008) reports positive and higher PPS for 416 Canadian firms from 2000 to 2005 compared with similar UK and US firms. Studies by Kaplan (1994), Kang and Shivdasani (1995), Angel and Fumas (1997), Cheng and Firth (2005) and Merhebi et al (2006), using German, Japanese, Spanish, Hong Kong and Australia companies, respectively, find similar positive and relatively strong PPS.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, and as an example of the case of research context potentially accounting for differences in the level of PPS that is observed, Sapp (2008) reports positive and higher PPS for 416 Canadian firms from 2000 to 2005 compared with similar UK and US firms. Studies by Kaplan (1994), Kang and Shivdasani (1995), Angel and Fumas (1997), Cheng and Firth (2005) and Merhebi et al (2006), using German, Japanese, Spanish, Hong Kong and Australia companies, respectively, find similar positive and relatively strong PPS.…”
mentioning
confidence: 96%
“…Consequently and in this study, we examine the extent to which these three ownership structures (block, director and institutional shareholdings) can have a moderating effect on the PPS. For example, greater monitoring that is often associated with block ownership can serve as a substitute for a good incentive alignment mechanism that is able to effectively restrain executive pay and improve the PPS (Cheng & Firth, 2005;Ding et al, 2015;Ntim, 2013b), although concentrated ownership can also have costs implications for minority shareholders, including entrenchment and extraction of private benefits. Block shareholders can, for instance, connive with executives to engage in fraudulent activities, such as 'tunnelling', or expropriate firm assets in the form of high pay at the expense of minority shareholders (Conyon & He, 2011, 2012, which can impact negatively on the PPS.…”
Section: The Effect Of Ownership Structure On the Ppsmentioning
confidence: 99%
“…8,9 However, other studies find no relation between executive pay and firm performance. 10,11 These inconsistent results can be explained by the fact that previous studies did not account for the effect of family influences on the pay-performance relations. In the Philippines, for example, the relation between managerial pay and performance only exists for firms not affiliated with a family group.…”
Section: Literature Reviewmentioning
confidence: 49%
“…Brossard et al, 2013;Gillan and Starks, 2000;Shleifer and Vishny, 1986), have led to the relationship between institutional directors and CEO compensation being analysed by earlier literature (e.g. Almazan et al, 2005;Cheng and Firth, 2005;Croci et al, 2012;Gómez-Mejía et al, 2003;Ozkan, 2011). The purpose of this research is to study how the presence of institutional directors on Spanish boards influences CEO compensation (total, fix and variable).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, previous literature has paid little attention to other board members: directors appointed by institutional investors (from now on institutional directors), since most previous literature bases principally on the association between institutional shareholding, acting as shareholders, and executive compensation (e.g. Cheng and Firth, 2005;Ezzeddine and Lamia, 2006;Hartzell and Starks, 2003).…”
Section: Introductionmentioning
confidence: 99%